A descriptive analysis of the microflora of Lake Bato and its relevance to biology teaching - Perez, Socorro A. 1933- (1975)
This research endeavors to provide biology teachers and students a descriptive analysis and classification of the existing microflora of Lake Bato. This work investigated the different genera of phytoplankton, microfungal flora, and bacteria. Based on the findings, it was evident that the lake is biologically productive and is highly recommended: as a place for field study of an aquatic ecosystem for high school and college biology classes; as an excellent source of fresh-water microscopic specimens for laboratory use; as a place for laboratory field work for students of Fishery High School; and as a place for demonstration purposes for fish culture and/or fish stocking for the manpower training in community development.
Thesis (M.A.T.)--University of the Philippines
Keywords: Marine flora -- Philippines -- Bicol; Biology -- Study and teaching -- Philippines